2000
DOI: 10.1177/101053950001200109
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus and Hepatitis C Virus Infections among Patients Attending Sexually Transmitted Disease Clinics, Regional 2, Thai land

Abstract: A cross-sectional study of 400 patients attending sexually transmitted disease (STD) clinics at The Venereal Diseases and AIDS Centers, Regional 2, Thailand, was conducted from January to December 1996 in order to investigate the antibody prevalence to human immunodeficiency virus (HIV) and hepatitis C virus (HCV) and to describe some epidemiological characteristics among HIV and HCV co-infected individuals. The studied patients were interviewed and their blood specimens were collected for determining anti-HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In Ratchaburi and Saraburi, over 9% were anti-HCV positive, and anti-HCV prevalence was greater in HIV-positive compared with HIV-negative FSWs. 39,40 In Ratchaburi, anti-HCV prevalence was 23% in women who had worked nine or more years as FSWs compared with 6.7% in women who had worked four years or less. 39 For comparison, anti-HCV prevalence was 1.5-2.1% in Thai blood donors during the same period.…”
Section: Hcv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ratchaburi and Saraburi, over 9% were anti-HCV positive, and anti-HCV prevalence was greater in HIV-positive compared with HIV-negative FSWs. 39,40 In Ratchaburi, anti-HCV prevalence was 23% in women who had worked nine or more years as FSWs compared with 6.7% in women who had worked four years or less. 39 For comparison, anti-HCV prevalence was 1.5-2.1% in Thai blood donors during the same period.…”
Section: Hcv Infectionmentioning
confidence: 99%
“…39 For comparison, anti-HCV prevalence was 1.5-2.1% in Thai blood donors during the same period. 40 One study in Thailand reported that three FSWs were IDUs; 40 none of the other studies in Africa, India or Thailand reported illegal drug use among FSWs.…”
Section: Hcv Infectionmentioning
confidence: 99%
“…Transmission is also associated with other parenteral exposures, such as tattooing, ear or body piercing, surgery, acupuncture, haemodialysis, occupational needle-stick injuries and other health-care procedures (Alter, 1994;Alter et al, 1990). Although the efficiency of HCV transmission through sexual or household contact is not yet understood entirely (Luksamijarulkul et al, 2000;Romanowski et al, 2003), the observation of closely related HCV sequences obtained from infected couples or sexual partners could be interpreted as evidence of HCV sexual transmission (Capelli et al, 1997;Chayama et al, 1995;Halfon et al, 2001;Healey et al, 1995;Kao et al, 1992Kao et al, , 2000Komine et al, 1999;Nakayama et al, 2005;Quer et al, 2003;Rice et al, 1993;Romanowski et al, 2003;Ross et al, 1999;Thaikruea et al, 2004;Yagura et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Current research related to coinfection of HCV and HIV may provide opportunities for screening among representative sample populations in the future. 20,21 …”
mentioning
confidence: 99%